Identifying psychosocial problems, needs, and coping mechanisms of adolescent Syrian refugees in Jordan - Al-Shatanawi, Tariq N.; Khader, Yousef; ALSalamat, Husam; Al Hadid, Lourance; Jarboua, Alaa; Amarneh, Basil; Alkouri, Osama; Alfaqih, Mahmoud A.; Alrabadi, Nasr (Frontiers in Psychiatry, 2023)
Background Refugees who have fled war zones are at a heightened risk of psychosocial problems that can impact their ability to function in day-to-day life and place a significant burden on the family structure. This study aimed to assess the psychosocial problems and needs and coping mechanisms of Adolescent Syrian refugees in Jordan. Methods Between October and December 2018, we conducted a qualitative study using semi-structured interviews with a sample of key and individual informants. Our sample included 20 primary healthcare professionals, 20 schoolteachers, 20 Syrian parents, and 20 adolescents aged 12–17 years. All interviews were transcribed verbatim, and we utilized thematic analysis to group, categorize, and analyze the original Arabic language transcripts. To ensure thorough analysis, we adopted a bottom-up inductive approach that covered the six-phase iterative process proposed by Braun and Clarke. Results The main psychosocial problems encountered by Syrian adolescents included stress, depression, loneliness, lack of a sense of security, isolation, aggressiveness, fear of war, and family disintegration. Almost all schoolteachers reported that they observed that Jordanian adolescents are more settled, self-confident, and financially stable relative to their Syrian peers. The Jordanian government and community were praised for their support, including education, recreational centers, health services, and awareness campaigns. Going to school, praying and reading the Holy Quran, listening to music, and talking to friends and engaging with them were reported as the main coping mechanisms. The majority of respondents said that more services are still needed for adolescents, including more places for entertainment, psychosocial support and psychological counseling, medical care, job creation, and providing health insurance. Conclusion Syrian refugees are aware of the psychological aspects of their situation, but they are not always able to access clinic-based humanitarian assistance for mental health and psychosocial support. Stakeholders must interact with refugees to learn about their needs and develop services that are appropriate for their culture.